Gate‐Tunable Resonant Raman Spectroscopy of Bilayer MoS2. Issue 35 (22nd June 2017) - Lu, Xin; Utama, M. I. B.; Wang, Xingzhi; Xu, Weigao; Zhao, Weijie; Owen, Man Hon Samuel; Xiong, Qihua
Abstract : The gate‐tunable phonon properties in bilayer MoS2 are shown to be dependent on excitation energy. Raman intensity, Raman shift, and linewidth are affected by resonant excitation, while a nonresonant laser does not influence the intensity significantly. The gate‐dependent Raman shift of A1g mode (either blue‐, red‐, or no‐shift) is a result of the combined effect of antibonding electron and resonant‐related decoupling effect. Although the decoupling effect cannot be directly measured due to the resonant background, it can be indirectly and qualitatively probed by observing A1g mode. This study on gate‐tunable resonant Raman spectroscopy has clarified the influence of carrier doping on phonon properties and demonstrates a new degree of freedom in manipulating phonons in 2D material systems. Abstract : The Raman intensity of A1g and E 2 g 1 modes in bilayer MoS2 is gate tunable at resonant excitation. Depending on the excitation laser, the gate tunable Raman shift of the A1g mode can be either blue‐, red‐, or no‐shift. A new degree of freedom in manipulating the phonons in 2D materials is demonstrated.